Type-2 immunity associated with type-1 related skin inflammatory diseases: friend or foe? - Migayron, Laure; Bordes, Sylvie; Closs, Brigitte; Seneschal, Julien; Boniface, Katia (Frontiers in Immunology, 2024)
Chronic inflammatory skin diseases are multifactorial diseases that combine genetic predisposition, environmental triggers, and metabolic disturbances associated with abnormal immune responses. From an immunological perspective, the better understanding of their physiopathology has demonstrated a large complex network of immune cell subsets and related cytokines that interact with both epidermal and dermal cells. For example, in type-1-associated diseases such as alopecia areata, vitiligo, and localized scleroderma, recent evidence suggests the presence of a type-2 inflammation that is well known in atopic dermatitis. Whether this type-2 immune response has a protective or detrimental impact on the development and chronicity of these diseases remains to be fully elucidated, highlighting the need to better understand its involvement for the management of patients. This mini-review explores recent insights regarding the potential role of type-2-related immunity in alopecia areata, vitiligo, and localized scleroderma.